Fa’aliyah Istikhdam Wasaith al-Tathbiq Wondershare Filmora fi Ta’lim al-Imla’: Dirasah Halah fi Mutawassith al-Shaff al-Hadi ‘Asyara bi Ma’had Hasanka Palangka Raya - Budiutomo, Sulistyo; Hamidah, Hamidah; Rahman, Nur Fuadi (Al-Wazan: Journal of Arabic Education, 2023)
This study aims to Knowing how the Imla learning process uses the Wondershare Filmora application, and Knowing whether audio-visual media is effectively used in Imla learning. This study uses a quantitative approach with a quantitative type of experiment. This type of research, One Group Pretest – Posttest only tests the effectiveness of Imla learning using video in one sample class. The research population was all students of class XI IPS SMA Hasanka Islamic Boarding School, amounting to 31 people. The sample of this study were 24 students of class XI IPS, because 7 other people moved schools and some were unable to attend. In this study, the results of the average grade XI IPS Hasanka Islamic Boarding school in the pre test were 60.4 and the post test was 69.1.This shows an increase in student learning outcomes in learning Imla using the Wondershare Filmora application by 9.